2016
DOI: 10.2119/molmed.2016.00023
|View full text |Cite
|
Sign up to set email alerts
|

TCR γ4δ1-Engineered αβT Cells Exhibit Effective Antitumor Activity

Abstract: T cell engineering with T cell receptors (TCRs) specific for tumors plays an important role in adoptive T cell transfer (ATC) therapy for cancer. Here, we present a novel strategy to redirect peripheral blood-derived αβT cells against tumors via TCRg4d1 gene transduction. The broad-spectrum antitumor activity of TCRδ1 cells in innate immunity is dependent on CDR3δ1. TCRg4d1-engineered αβT cells were prepared by lentiviral transduction and characterized by analyzing in vitro and in vivo cytotoxicity to tumors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…We amplified full-length TCRδ1 with GTM sequence from cDNAs of gastric cancer tissues and TCRγ4 chains from cDNAs of gastric tumor-derived γδ TILs, which were then cloned into pREP9 and pREP7 vectors for sequence analysis. We found that TCRγ4δ1-engineered αβT cells exhibited significant cytotoxicity against HepG2 and BGC-803 tumor cells and were validated on mouse tumor models [89].…”
Section: Therapeutic Opportunities Brought By Tumor-associated Protei...mentioning
confidence: 84%
“…We amplified full-length TCRδ1 with GTM sequence from cDNAs of gastric cancer tissues and TCRγ4 chains from cDNAs of gastric tumor-derived γδ TILs, which were then cloned into pREP9 and pREP7 vectors for sequence analysis. We found that TCRγ4δ1-engineered αβT cells exhibited significant cytotoxicity against HepG2 and BGC-803 tumor cells and were validated on mouse tumor models [89].…”
Section: Therapeutic Opportunities Brought By Tumor-associated Protei...mentioning
confidence: 84%
“…The proliferation of γδT cells was detected by CellTrace™ CFSE Cell Proliferation Kit (Invitrogen™, Thermo Fisher, USA) as described previously (21, 22). In brief, γδT cells were amplified in vitro with anti-TCR PAN γ/δ monoclonal antibody (Beckman Coulter, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, endogenous ab TCRs were downregulated after the transduction of gd TCRs, leading to a lack of alloreactive response (147). Besides, several types of tumor specific CDR3d-grafted gd TCRs were also used to modify ab T cells and exhibited significant antitumor effects (148,149). Moreover, a novel antibody-TCR (Ab-TCR) modified ab T cells, combining Fabbased antigen recognition with gd TCR signaling, showed a similar cytotoxicity and a less cytokine release comparing with CD28/CD3z CAR-T cells (150).…”
Section: Gd Tcrs Transfer To Ab T Cellsmentioning
confidence: 99%